Thomas Francis Galwey papers - Galwey, Thomas Francis, 1846-1913.
Three volume diaries (1861-1864) concerning Galwey's Civil War experiences in Virginia as a member of the Ohio Infantry, 8th Regiment. Also includes correspondence, clippings, and programs (1864-1908).
Union soldier.
Collection material in English.
Keywords: United States. -- Army. -- Ohio Infantry Regiment, 8th (1861-1865); Virginia -- History -- Civil War, 1861-1865.; Soldiers